Evaluating the Performance, Emissions, and Combustion Characteristics of CRDI Diesel Engines Using Pine Oil Blends as a Sustainable Fuel Alternative - Manikandan Chandrasekaran; C. Syed Aalam (International Journal of Machine Systems and Manufacturing Technology, 2025)
The performance of Common Rail Direct Injectors (CRDI) diesel engines is examined in this study in relation to interacts of pine oil used as an alternative fuel. Finding sustainable fuel solutions is of paramount importance given the growing environmental concerns and the decreasing supply of fossil fuel resources. Pine oil, obtained from resin tapped from pine trunks and processed through steam distillation to separate turpentine from rosin, offers a viable alternative. This study evaluates ways pine oil mixes affect engine performance variables including brake-specific energy use, thermal efficiency, and emissions of pollutants like carbon dioxide, smoke, and sulfur dioxide. In order to comprehend the combustion properties of pine oil blends, combustion analysis methods such as heat release rate assessment and in-cylinder pressure monitoring are also used. The results contribute to sustainable energy plans in the transportation industry by offering insightful information on the viability and difficulties of using pine oil as an alternate fuel for CRDI diesel engines.
Keywords: Common rail direct injection; Diesel engine; Pine oil; combustion; emission